HUBUNGAN TINGKAT PENDAPATAN DENGAN TINGKAT KONSUMSI MASYARAKAT DI KECAMATAN BONTONOMPO KABUPATEN GOWA - Sanusi Am, Sanusi Am; Ansar, Ansar (Jurnal Ekonomi Balance, 2014)
The purpose of this study is to explain the relationship between the level of income with the level of public consumption in District Bontonompo Gowa District. This research uses time series data obtained from Central Bureau of Statistics (BPS). The analytical tool used is Pearson correlation formula with the help of SPSS For Windows Release 16. The results concluded that the income level has a significant relationship to the level of public income in District Bontonompo Gowa Regency. It is expected that the Gowa Regency government can pursue programs that can encourage the creation of more and more diverse employment so that the communities of each bias can earn a decent income and meet their consumption needs